2020
DOI: 10.1177/0300060520965353
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between lipoprotein(a) gene polymorphisms and calcific aortic valve disease and coronary heart disease in Han Chinese

Abstract: Objective To investigate the relationship between lipoprotein(a) gene ( LPA) polymorphisms and calcific aortic valve disease (CAVD) and coronary heart disease (CHD) in Han Chinese. Methods A total of 148 patients were recruited (n = 71 with CAVD and n = 77 with CHD) based on a diagnosis achieved using color Doppler echocardiography, coronary angiography, or computed tomography angiography. Seventy-one control individuals without CAVD or CHD were also recruited. Biomarkers including levels of lipoprotein(a) [Lp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…In addition to the classic risk factors such as age, smoking, drinking, hypertension, diabetes, and hypercholesterolemia [ 9 ], a large number of studies have confirmed that genetic factors play an important role in the occurrence and development of CHD [ 10 ]. Besides, many genetic variants such as LPA [ 11 ], CYP24A1 [ 12 ], CYP2C19 [ 13 ], PNPLA3 I148M [ 14 ], and IL-7 / 7R [ 15 ] can significantly affect the susceptibility of CHD.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the classic risk factors such as age, smoking, drinking, hypertension, diabetes, and hypercholesterolemia [ 9 ], a large number of studies have confirmed that genetic factors play an important role in the occurrence and development of CHD [ 10 ]. Besides, many genetic variants such as LPA [ 11 ], CYP24A1 [ 12 ], CYP2C19 [ 13 ], PNPLA3 I148M [ 14 ], and IL-7 / 7R [ 15 ] can significantly affect the susceptibility of CHD.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other populations, the epidemiology of Lp(a) in the Chinese population shows a unique differentiation. Dong et al 12 found a genetic variation in Lp(a) at single nucleotide polymorphisms (SNPs) rs6415084, rs3798221, and rs7770628, which may cause the differentiation of high Lp(a) plasma levels among the Han Chinese population. A cross-sectional study of 3,462 case and 6,125 control subjects also suggested that the Lp(a) distribution in the Chinese Han population differs from that in Caucasian populations, and high Lp(a) levels can be modified by some risk factors in the Chinese Han population.…”
mentioning
confidence: 99%
“…However, previous studies report the association of this polymorphism with the LP(a) level [ 28 30 ]; unfortunately, the Lp(a) level was not measured in this study.…”
Section: Discussionmentioning
confidence: 57%